A Critical Examination for the Pricing of Eculizumab and Efgartigimod in Myasthenia Gravis - Paul C. Langley (University of Minnesota Libraries Publishing, 2021)
The purpose of this commentary is to focus on the downside of assumption-driven simulation modeling, the potential creation of a multitude of competing models, the mathematically impossible quality adjusted life year (QALY) and the failure to observe the axioms of fundamental measurement in mapping ordinal EQ-5D-5L preferences from the ordinal Quantitative Myasthenia Gravis (QMG) score. A second aspect of this commentary is to propose standards that should be set for the creation and evaluation of value claims in health technology assessment, in particular need fulfillment quality of life (QoL), that meet the demarcation test to distinguish science from non-science. The result is that the present ICER pricing claims for eculizumab and efgartigimod in myasthenia gravis should not be applied without consideration of more relevant evidence.